PENGEMBANGAN JARINGAN INTERNET WIRELESS DENGAN WIFI OVERVIEW PADA OBYEK WISATA BLANGSINGA WATERFALL - I Made Ari Dwi Suta Atmaja; I Nyoman Gede Arya Astawa; Putu Gde Sukarata (JURNAL INTEGRASI, 2019)
Blangsinga Waterfall is one tourist attraction with very extreme geographical conditions, where the area has not covered GSM signals as a result tourists can not access the Internet network. The purpose of this research is to determine the spot of Wireless and Hotspot network infrastructure and then to measure signal strength for tourism area coverage. Based on field analysis determined 3 (three) points for network construction and placement of Access Point as Hotspot. Implementation begins with building a LAN network. Then for scanning channel and signal access point testing used Wifi Overview tool. Signal strength testing is performed around the area of ​​the resort by taking a distance of 5m, 10m, and 15m in all directions from the Access point is placed. The result is the establishment of internetworking for Blangsinga Waterfall tourism area. The next result is the internet access where all the tourist areas are covered wifi signal. With the development of internet infrastructure, tourists get easier communication access and management of tourist attractions can develop other facilities based on internet network that has been built.